NEGOTIATING MUSLIM IDENTITY IN THE AGE OF GLOBALIZATION: A LITERATURE REVIEW - Nadia Alifa Nur Aenida; Hanifa Mawadah; Doddy S. Truna; Erni Haryanti Kahfi (Islamic Studies Journal (ISLAM), 2025)
Globalization has had a considerable influence on Muslim identity, especially in the social, cultural, and technological fields. This article aims to discuss how Muslims not only understand their religious identity, but also guard it from world changes and technological advances. By reviewing various current literature sources that discuss how Muslim identity is formed and developed in an ever-changing environment. This research shows that Muslim identity is not something fixed, but is formed through an ongoing process of adjustment between the Islamic values that have been traditionally inherited and the influence of modernity that has emerged in the era of globalization. Muslims have shown an active role by responding to gender-related issues, fighting discrimination against Islam, and overcoming negative stereotypes, while utilizing the use of digital media as an easier means of conveying and strengthening religious identity. Thus, understanding Muslim identity today requires examining the diversity of Muslim experiences in various contexts, as each group faces distinct challenges and expresses its religious identity in unique ways within a global society.